The personal distribution of income and imputed rent: A cross-national comparison for the UK, West Germany, and the USA - Joachim R. Frick; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This article deals with income advantages derived from owner occupied housing (Imputed Rent, IR) and their impact on the personal income distribution. Following a brief description of different methods with which to calculate IR in household surveys, we conduct a cross-national comparative study based on micro-data from the British Household Panel Study (BHPS), the German Socio-Economic Panel (SOEP), and the US Panel Study of Income Dynamics (PSID). We find distinct differences between the Anglo-Saxon countries and Germany in terms of prevalence and extent of IR as well as in terms of the impact on the overall income distribution. In all three countries, however, using IR in measures of old age provision improves the quality of economic well-being assessment for the elderly.
Keywords: 330; Personal Income Distribution; Owner Occupied Housing; Imputed Rent; Old Age Provision; Einkommensverteilung; Wohneigentum; Rente; Schätzung; Deutschland; Vereinigte Staaten; Großbritannien